Behavior of Glasses Users in Refractive Disorders with Theory of Reasoned Action Approaches - Raimah Anbara; Bakri Mat; Salwani Arbak (STIKes MERCUBAKTIJAYA, 2022)
Issues and Problems : Glasses are a safe method for correcting refractive errors of the eye. A person with refractive error makes the decision to buy and use glasses because of various factors. One of them is caused by interests that are influenced by norms or other people's views about wearing glasses. Objective : This study was conducted to analyze the behavior of eyeglass users with refractive errors using the theory of Reasoned Behavior. Method: Qualitative method that utilizes primary and secondary sources in the form of official reference sources, and other printed and unprinted sources, as well as online sources that have been used. Finding: The results show that although glasses are a necessity for people with refractive errors, their behavior is influenced by the intentions of the users of the glasses. And the intention to get a visual aid is also influenced by the subjective attitudes and norms of the glasses user. Attitudes are formed from the beliefs or beliefs held about glasses and the evaluation of their use in helping the user's appearance. Meanwhile, norms are formed from norms that are believed to be related to the use of tools as a tool for refractive errors and motivation from the closest people and medical personnel. Recomendation: people with refractive errors are advised to increase their knowledge and understanding of the use in treating refractive disorders which are the controllers of negative norms owned by users so that the goal of overcoming visual disturbances and reducing eye damage can be carried out properly. Health workers are expected to contribute in providing information for the myths that exist in the community regarding the use of glasses